Pengaruh media pembelajaran berbasis WEB terhadap peningkatan keterampilan praktikum asuhan kala II persalinan mahasiswa DIII kebidanan - Wiriyanti, Muridah; Syarif, Syafruddin; Ahmad, Mardiana; Prihartini, Sabrina Dwi; Wahyuni, Indah Sri (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Web based learning media is used to support systems that walk conventionally, web based learning media can enhance learning more effectively because with a web based display to help students to be able to participate practicum independently and can support practical activities before entering the laboratory. This study aims to determine the effect of web-based learning media on improving the skills care the stage II of childbirth DIII Midwifery studentsResearch methods: This study uses a Quasi Experiment with a non equivalent control group design. The population of all students of the Pelamonia Midwifery Academy VII Wirabuana Makassar in 2019. The sample in this study is the second semester students of the third semester of the Pelamonia Midwifery Academy VII Wirabuana Makassar, amounting to 151 people, divided into 2 groups intervention and control.  The intervention group numbered 32 people, control 40 people. The sampling technique is purposive sampling. Each group was given a skills pre-test whose assessment was in accordance with the observation sheet on the second stage of labor care procedures. Then the intervention group was given web-based learning media for 1 meeting with 2x50 minutes time. At the end of the meeting a post-test was conducted. Using paired sample t-test.           Results: Statistical test results showed that there were differences in the results of measurement I and measurement II of childbirth care skills in the control group (p <0.05) and contributed 46.3%. In the intervention group there were differences in skills before and after the provision of web-based learning media (p <0.05) and contributed 91.7%, in improving the skills of the second semester Midwifery D-III students regarding second stage of labor.Conclusion: The results of data analysis and evaluation results on web-based learning media have an effect on improving the skills of stage II of childbirth care in Midwifery D-III